Type 2 Diabetes Mellitus Risk in Physical Exercise Program Users - José Ander Asenjo Alarcón (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Background: type 2 diabetes mellitus is escalating to worrying levels in public health, due to its initial silent manifestation in the population. It is wise and relevant to study the risk factors that contribute to its occurrence in few investigated demographic contexts. Objective: to determine the relationship between risk factors and type 2 diabetes mellitus in Exerfis-D physical exercise program users in Chota city, Cajamarca. Methods: an observational, cross-sectional study was carried out in 112 users identified in a physical exercise program. Risk factors for type 2 diabetes mellitus were determined with a diagnostic interpretation guide adapted from the American Diabetes Association, the Peruvian Endocrinology Society, and the Ministry of Health. Absolute and relative frequencies, the prevalence odds ratio (ORP), the population etiological fraction and the Chi square test of independence were determined with a confidence level of 95 %. Results: the most frequent risk factors in the study were altered abdominal girth in women (96.8 %) and men (78.9 %), decreased HDL-C (58 %) and obesity (50.9 %); the prevalence of type 2 diabetes mellitus was 42.9 %; obesity constitutes 2.28 times the risk for this condition; the population etiological fraction indicates that obesity and altered female abdominal girth contribute to 35.09 % and 53.2 % of diabetes cases in the study population, respectively. Conclusion: the type 2 diabetes mellitus risk factor in the studied users was obesity (ORP = 2.28), which obtained a statistically significant relation with diabetes (p <0.05).